Towards Predicting Ad Effectiveness via an Eye Tracking Study - Christoforou, Christoforos; Zaphiris, Panayiotis; Michailidou, Eleni (My University, 2014)
This paper presents the pilot study of a project for which the main aim is to implement an evaluation methodology service for the identification of the best locations on Cypriot web space based on eye tracking studies. Advertising budget, social demographics and web usage are some of the factors that are being considered. During this pilot study, a description in existing patterns of advertisement placement on websites is first presented. Then we present the methodologies of two pilot studies where user data are collected with the use of eye tracking technologies in order to understand how users look at Web advertising and how effective each location is as well as Marketers’ questionnaire. Stimuli were three Cypriot websites with advertisements of various types and three locations: ads being static and animated, types being skyscraper and display ads and location varied around the page. Eye-tracking data are compared to ad choices of marketing managers in Cyprus who rated the ad position and it’s attention value. Results demonstrate the correlation between user attention, advert types and the value as rated by marketers. This pilot study revealed conclusions that could form the basis towards predicting ad effectiveness of webpages with the use of ad number, location, size, and type.
Keywords: Advert attention; Online advertising; Eye tracking; CPM